2020
DOI: 10.26633/rpsp.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

Identificación y perfil de sensibilidad de Candida spp. aisladas de hemocultivos en hospitales de Paraguay

Abstract: Objetivo. Reportar las especies identificadas en candidemias aisladas en hospitales del país, su distribución según los grupos etarios y determinar la sensibilidad a fluconazol, voriconazol y anfotericina B. Métodos. Estudio retrospectivo de candidemias reportados por siete hospitales al Laboratorio Central de Salud Pública en el período 2010 - 2018. La identificación y el antifungigrama fueron realizados en el sistema automatizado Vitek®2. Resultados. Se informaron 520 casos de candidemias. Las especies preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…glabrata (9.5%). In Paraguay, data from 520 cases of candidemia showed prevalence values of C. albicans : 34.4%, C. parapsilosis: 30.4%, C. tropicalis : 25.4%, C. glabrata : 4.8%, and C. krusei : 2.1% [ 18 ]. In Colombia, three reports indicated variable proportions of C. albicans , C. parapsilosis, C. tropicalis and low or total absence of C. glabrata [ 19 , 20 , 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…glabrata (9.5%). In Paraguay, data from 520 cases of candidemia showed prevalence values of C. albicans : 34.4%, C. parapsilosis: 30.4%, C. tropicalis : 25.4%, C. glabrata : 4.8%, and C. krusei : 2.1% [ 18 ]. In Colombia, three reports indicated variable proportions of C. albicans , C. parapsilosis, C. tropicalis and low or total absence of C. glabrata [ 19 , 20 , 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Nosocomial infections are closely associated with a relevant attribute of virulence of many Candida species; their ability to form biofilms confers an intrinsic resistance against various antifungal drugs and mechanisms of immune reaction [ 20 ]. The biofilms grow attached to medical devices or host tissues [ 18 ] and in addition to their difficult eradication, the final phase involves dispersion of non-adherent cells, which results in the initiation of newer biofilms and further dissemination to other tissues [ 52 , 53 ]. Atiencia-Carrera et al [ 66 ] reported one extensive meta-analysis of 214 studies about the rates, types and antifungal resistance of Candida biofilms among hospitalized patients between 1995 and 2020.…”
Section: Pathogenesis Of Invasive Candidiasismentioning
confidence: 99%
“…Otros autores hallaron 100 % de sensibilidad de C. albicans frente a voriconazol (16,24,33) . Con relación al trabajo publicado recientemente en nuestro país, por Aguilar et al en aislamientos provenientes de hemocultivos, la resistencia al voriconazol que encontramos es elevada (34) . Probablemente la mayor resistencia es debida a la utilización frecuente de azoles en la población estudiada, tanto para profilaxis como para el tratamiento.…”
Section: Especies De Candidaunclassified